2020
DOI: 10.1186/s12877-020-01662-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing and non-prescribing in nursing home residents with signs and symptoms ascribed to urinary tract infection (ANNA): study protocol for a cluster randomized controlled trial

Abstract: Background Antibiotic overprescribing for suspected urinary tract infection (UTI) in nursing homes (NHs) is common. Typical clinical scenarios in which antibiotics are inappropriately prescribed include response to nonspecific signs and symptoms and/or a positive urine test in the absence of symptoms referable to the urinary tract. These and other scenarios for inappropriate antibiotic prescribing were addressed in a recent international Delphi study which resulted in the development of a decision tool for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
(35 reference statements)
2
16
0
Order By: Relevance
“…Study designs of included articles are shown in the second column of Table 2 . Studies [ 12 , 14 , 16 , 17 , 20 , 21 ] were mainly focused on diagnosing UTIs in patients, while studies [ 18 , 19 ] investigated the treatment approaches of UTI patients. The rest of the studies [ 13 , 15 ] assessed UTI prophylaxis and asymptomatic bacteriuria (UTI), as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study designs of included articles are shown in the second column of Table 2 . Studies [ 12 , 14 , 16 , 17 , 20 , 21 ] were mainly focused on diagnosing UTIs in patients, while studies [ 18 , 19 ] investigated the treatment approaches of UTI patients. The rest of the studies [ 13 , 15 ] assessed UTI prophylaxis and asymptomatic bacteriuria (UTI), as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The rest of the studies [ 13 , 15 ] assessed UTI prophylaxis and asymptomatic bacteriuria (UTI), as shown in Table 2 . There were five studies [ 15 , 16 , 18 , 19 , 21 ] performed at nursing homes in the USA, two each in Norway [ 13 , 17 ] and the Netherlands [ 12 , 20 ]. Study [ 14 ] was conducted at nursing homes in Italy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, guideline recommendations alone do not prevent treatment of non-specific symptoms and additional approaches to improve antibiotic prescribing behaviour are warranted. Involvement, education, and coaching of both physician and nursing staff have already been presented as strategies to improve antibiotic stewardship [ 19 , 26 , 27 , 28 , 29 , 30 , 31 ]. Additional strategies include providing communication tools to nurses to improve effective communication among healthcare workers [ 32 ] and interventions directed at appropriate urine culturing [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recommended guideline, inappropriate antibiotic prescriptions persists. A strategy to enhance appropriate antibiotic prescriptions in this setting is to improve the diagnostic process of suspected UTI in older adults, for example, by implementing a decision tool that automatically generates treatment advice into the electronic health record [ 19 ]. For any antibiotic stewardship strategy to improve prescribing behaviours for UTIs, more insight into antibiotic treatment decisions and influencing factors is essential.…”
Section: Introductionmentioning
confidence: 99%